Gastrocytoprotection by colloidal bismuth subcitrate (De-Nol) and sucralfate. Role of endogenous prostaglandins. Issue 2 (February 1987) - Konturek, S J; Radecki, T; Piastucki, I; Brzozowski, T; Drozdowicz, D
Abstract : This study compares the gastroprotective effects of colloidal bismuth subcitrate (De-Nol) with those of sucralfate and a methylated analogue of prostaglandin E2 (PGE2) against acute gastric lesions induced by acidified aspirin and absolute ethanol in rats. Both De-Nol and sucralfate given orally prevented dose dependently the formation of gastric lesions by these ulcerogens, De-Nol being, respectively, twice and seven times more potent, on a weight basis, than sucralfate. As the gastroprotective activities of both De-Nol and sucralfate on ethanol lesions can be reversed by pretreatment with indomethacin and as De-Nol and sucralfate increase the mucosal generation and luminal release of PGE2, we postulate that mucosal prostaglandins may be involved in the mechanism of action of these drugs on the gastric mucosa.